A Smartphone‐Enabled Portable Digital Light Processing 3D Printer (Adv. Mater. 35/2021). Issue 35 (2nd September 2021) - Li, Wanlu; Wang, Mian; Mille, Luis Santiago; Robledo Lara, Juan Antonio; Huerta, Valentín; Uribe Velázquez, Tlalli; Cheng, Feng; Li, Hongbin; Gong, Jiaxing; Ching, Terry; Murphy, Caroline A.; Lesha, Ami; et al.
Abstract : 3D Printing In article number 2102153, Khoon S. Lim, Yu Shrike Zhang, and co‐workers present a smartphone‐enabled Digital Light Processing (DLP) 3D printer based on a smartphone‐powered projector and a customized touchscreen smartphone app, featuring portability, modularity, and an easy‐to‐use interface. Through printing with commercial resins and hydrogel‐based (bio)inks, it is applied to the fabrication of medical implants, in situ bioprinting, and integration with 3D object‐scanning capability.